Efforts to Improve Understanding of the Main Material of Morals Through the Problem Based Learning Model for Class VIII Students of SMP Negeri 2 Tambusai - Harahap, Mariah (Indonesian Journal of Basic Education, 2024)
This class action research aims to improve students' understanding of the material of Praiseworthyhlak through the application of the Problem Based Learning (PBL) learning model. The research subjects were students of class VIII SMP Negeri 2 Tambusai in the odd semester of the 2024/2025 academic year, totalling 30 students. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Data collection instruments used comprehension tests and student activeness observation sheets. The results showed an increase in student understanding after the application of the PBL model. In the pre-cycle, the average student score was 65 with 36.7% completeness. After the application of PBL in cycle I, the average score increased to 73.3 with 66.7% completeness. In cycle II, there was a significant increase with an average score of 82 and a completeness rate of 90%. Based on these results, it can be concluded that the PBL model is effective in improving understanding of the material of Morals.